Dampak Perceraian terhadap Anak Perspektif Psikologi Pendidikan - Rohimah, Siti; Nurachman, Azhar; Setiawan, Rizka (AHKAM, 2024)
The harmonious relationship between parents and children is crucial in a family, as the harmony within the household significantly influences the growth, development, and education of children. However, it is inherent in human nature that happiness, suffering, pain, joy, illness, harmony, and conflict are events that always come and go in human life. This study aims to describe the impact of divorce on children's psychological development. Using a literature review research approach, the author explains that divorce is not the end of the marital relationship, but parents who have divorced need to continue thinking about the future development and education of their children, as divorce not only affects their children but also impacts the spouses, with the greatest impact being on children's psychological development. The results of this study show that divorce has a negative impact on children's psychological development, as the overall psychological development of children whose parents are divorced is significantly disrupted. Furthermore, the negative impact of divorce includes a lack of love and attention from both parents. Family integrity is necessary to support children's psychological development and education. The lack of attention and affection towards children due to their parents' divorce creates feelings of anxiety, confusion, restlessness, shame, and sadness.